Do Private Water Utility Operators Care about Regulatory Agencies in Developing Countries? - Bertomeu-Sanchez, Salvador (World Bank, Washington, DC, 2017)
This paper shows that the creation of an independent regulatory agency is often not a necessary or sufficient condition to help attract private participation in the operation and financing of the water and sanitation sector in developing countries. However, the odds of an impact are significantly higher for Latin American and Caribbean countries and, to a lesser extent, Eastern European countries, than for any other region. Higher income levels and higher prices are also correlated with higher effectiveness of independent regulatory agencies in attracting private sector financing. Analysis of the impact on various types of public-private partnership contracts shows that, at the margin, independent regulatory agencies are irrelevant in general, for the contract choice, except for greenfield projects, for which such agencies may be counterproductive at the margin.